True north : a memoir - Conway, Jill K., 1934- (New York : Alfred A. Knopf, 1994)
With all the openness to life, all the largeness of spirit, that made her girlhood memoir, The Road from Coorain, an acclaimed - and beloved - bestseller, Jill Ker Conway continues her story.
She was twenty-five when we left her, driven by a hunger to know and to understand, boarding a plane that would carry her far from her Australian homeland. As True North begins she lands, appropriately enough, in a hurricane, in New York.
And is soon at Harvard, a graduate student in history experiencing both exhilaration and culture shock; discovering among friends of many backgrounds an easier sociability than she has ever known; delighting in classes that seem charged with energy, and in the perception that ideas were being taken seriously - yet still feeling like an extraterrestrial on the American planet.
We see her joining with five other women to form a household that becomes an "almost magical," hilarious, and harmonious community - the community that functions as her family when she meets the Harvard professor and housemaster who will become her husband, John Conway, himself a historian, Canadian born and bred, decorated for heroism in World War II - the complex man whose mind and spirit complement her own.
We see them marrying and learning to live together - during a year at Oxford, in Rome, and as they settle into the new world of Canadian university life - happy with each other, while coping, not always well, with her classically obsessive thesis writing, her as-yet-unresolved conflict with her mother, his periodic bouts of depression, and her realization that even though John's integrity, courage, and devotion to humanistic learning have become the compass point - the true north - by which she steers, there will be times when she has to navigate alone.
Keywords: Conway, Jill K., -- 1934-; Smith College -- Presidents -- Biography